Stress Among Working Women: A Silent Serpent - Lakhute, Sadhana vitthalrao; Band, Rahul Mohanrao; Rajasekaran, Praveen Kumar (National Journal of Community Medicine, 2024)
Stress among females is double fold than males in developing countries like India. Stress of working women not only impacts the mother but also the family as a whole. Stressors arise in women from the workplace and from their own homes. Stress can be caused by stressors in the home such as unexpected guests and family relations.In countries like Spain have started 4 day per week work hours in pilot basis to reduce stress and improve productivity.. This should be done universally to tackle the stress among working population predominantly females..Stress is unavoidable nowadays and the ways to tackle them is only by whole hearted connection with family and friends outside the working hours..A less stressed life of a women will bring more prosperity to the family as a whole..This is the reason stress among working women is called SILENT SERPENT.